Clinical Significance of De Novo and Inherited Copy‐Number Variation. Issue 12 (10th October 2013) - Vulto‐van Silfhout, Anneke T.; Hehir‐Kwa, Jayne Y.; van, Bregje W.M.; Schuurs‐Hoeijmakers, Janneke H.M.; Meader, Stephen; Hellebrekers, Claudia J.M.; Thoonen, Ilse J.M.; de, Arjan P.M.; Brunner, Han G.; Webber, Caleb; Pfundt, Rolph; de, Nicole; et al.
<x xml:space="preserve">Abstract</x> DNA samples from 5, 531 patients with ID/MCA were analyzed with a 250K SNP array for detection of copy number variants (CNVs). Comparison of phenotype features of patients with de novo (yellow), inherited (red), and without CNVs (blue) showed that severe phenotypes, including abnormal head circumference and organ malformations, were enriched in patients with de novo CNVs, both in comparison to patients without CNVs as well as patients with inherited CNVs. Remarkably, patients with inherited CNVs had significantly more facial dysmorphisms and a higher De Vries score (measure of clinical severity) compared with patients without CNVs, suggesting that the milder clinical features can also be related to the presence of inherited CNVs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>